The impact of parents anonymous on child safety and permanency. (May 2021) - Burnson, Cynthia; Covington, Sarah; Arvizo, Bertha; Qiao, Jun; Harris, Elizabeth
Highlights: Parents anonymous participation predicts reductions in child maltreatment. Improvements in child maltreatment were sustained over a 12-month period. Without intervention, the children in this program are at high risk of maltreatment. Abstract: Introduction: Parent support groups are a widely adopted form of child abuse and neglect prevention. Parents Anonymous began as a family-strengthening organization and launched a parent support program that provides direct services to parents to improve parenting and coping skills, strengthen social connections, and build resiliency. A quasi-experimental design was used to examine the effectiveness of Parents Anonymous in improving outcomes in child safety and permanency in two large California counties. Methods: We compared subsequent child welfare involvement outcomes between a sample of parents who received Parents Anonymous services to a sample who did not, all of whom had been involved in the child welfare system (N = 17, 482). The samples were identified using exact matching. A total of eight outcomes were evaluated using a binary logistic regression model: subsequent child welfare outcomes of referral, investigation, substantiation, or child removal within two post-treatment periods (six and 12 months). Program impact was assessed with a binary logistic regression model. For double-robust analysis, variables that were used in the matching process were also used in the impact analysis. The independent variables included treatment status, age of youngest child in days, income, number of prior investigations, and whether or not the index referral was substantiated for physical abuse. Baseline equivalence was established between the two samples prior to the impact analysis. Results: Two outcomes were statistically significant ( p ≤ 0.05). A referral for child abuse or neglect and a substantiated child abuse or neglect finding were both significantly less likely in the treatment group than the comparison group at 12 months post-treatment. No other statistically significant results were identified in the analysis. Conclusions: While there is more to learn about the program mechanisms of causality, the findings suggest that participation in Parents Anonymous may have a positive, long-term impact on improving child safety among parents involved in the child welfare system.